Research Productivity in Surgery from Pakistan: A Bibliometric Analysis (2001-2022) - Muhammad Imran, (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To evaluate the main bibliometric indicators and analyze the development of surgery-related research in Pakistan. Methods: This was a descriptive bibliometric analysis. The Web of Science (WoS) database was used to extract data. The study analyzed all English-language articleson surgery research from Pakistan from 2001 to 2021. To analyze the data, R-Bibliometrics software was utilized. Results: There were 748 articles, with 163 sources,11973 authors, and 39.97% international co-authorship. Annual growth rate was 9.91%. International Journal of Surgery, International Journal of Surgery Case Reports, World Journal of Surgery, and World Neurosurgery were the most leading sources, with >40 publications each. Overall, an increasing trend was observed during last 10 years, including 72.9% of all publications. Zafar H, Haider AH, Khan S, Zafar SN, &Enam SA published >20 articles. Enam SA had highest TC (1796), followed by Elkelany A, and Hanrahan M, 845 each. Aga Khan University Hospital and Aga Khan University displayed >200 affiliations. Karachi had 50% top ten most affiliated institutes. Mostly, funding agencies were international, except HEC which was leading from Pakistan. The articles published by Agha RA had highest citations. Conclusions: Policymakers need to redesign research policies to increase faculty members' research productivity. Support is required in funding sources, professional development, and collaboration to produce high impact research. The findings could be useful for surgeons and researchers who want to study surgery-related research trends in the region including Pakistan. Certain practical implications can be deducted from this research. Influential authors and institutions can be identified which can help in decision-making regarding potential opportunities and collaborations. Identifying emerging trends and gaps would be helpful for researchers in the field. Keywords: Surgery, Research, Pakistan, Bibliometrics, Web of Science